Interpreting Inequality Measures and Changes in Inequality - John Creedy (New Zealand Government, The Treasury, 2014)
This paper explores, in the context of the Atkinson inequality measure, attempts to make interpretations of orders of magnitude transparent. One suggestion is that the analogy of sharing a cake among a very small number of people provides a useful intuitive description for people who want some idea of what an inequality measure `actually means'. In contrast with the Gini measure, for which a simple `cake-sharing' result is available, the Atkinson measure requires a nonlinear equation to be solved. Comparisons of `excess shares' (the share obtained by the richer person in excess of the arithmetic mean) for a range of assumptions are provided. The implications for the `leaky bucket' experiments are also examined. An additional approach is to obtain the `pivotal income', above which a small increase for any individual increases inequality. The properties of this measure for the Atkinson index are also explored.
Keywords: D31; D63; 330; Inequality; Atkinson Measure; Excess Share; Soziale Ungleichheit; Messung; Einkommensverteilung; Konzentrationsmaß; Experiment; Theorie